The role of parental child relationship on phubbing is mediated by self-regulation in elementary school students - Azizah, Wanda (Universitas Muhammadiyah Malang, 2024)
Nowadays, children from toddlers to teenagers also use and enjoy the various functions offered by smartphones. Children who have been diagnosed with smartphones have difficulty stopping screen time. So many elementary school children often do phubbing. Phubbing is the act of focusing only on the world displayed on your smartphone and ignoring the people around you. The aim of this research is to determine whether there is a role between parent-child relationships and self-regulation in phubbing behavior in elementary school students. This research uses a correlational quantitative method using path analysis and using a non-probability sampling method with a purposive sampling technique. The subjects of this research were 270 active students with the subject criteria being (1) children aged 10 to 13 years who have smartphones, (2) use smartphones for more than 2 hours per day and (3) have applications. The results of the study showed that the relationship between parents and children mediates self-regulation of phubbing on phubbing behavior. This research shows that the parent-child relationship towards phubbing has a strong influence so that with high self-regulation children tend to be less likely to engage in phubbing behavior.